2015
DOI: 10.1371/journal.pone.0125870
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Rice L-Galactose Pathway: Evaluation of the Effects of Transgene Overexpression on Ascorbate Accumulation and Abiotic Stress Tolerance

Abstract: Ascorbic acid (AsA) is the most abundant water-soluble antioxidant in plants, and it plays a crucial role in plant growth, development and abiotic stress tolerance. In the present study, six key Arabidopsis or rapeseed genes involved in AsA biosynthesis were constitutively overexpressed in an elite Japonica rice cultivar. These genes encoded the GDP-mannose pyrophosphorylase (GMP), GDP-mannose-3',5'-epimerase (GME), GDP-L-galactose phosphorylase (GGP), L-galactose-1-phosphate phosphatase (GPP), L-galactose deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 44 publications
4
58
1
5
Order By: Relevance
“…Studies have demonstrated that the synthesis of AsA plays important roles in the response of plants to salt stress [25, 3840]. To further analyze the role of AsA in OsVTC1-1 -mediated enhancement of salt tolerance in rice, we examined the effect of AsA on salt tolerance of OsVTC1-1 RI seedlings with supplying exogenous AsA.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that the synthesis of AsA plays important roles in the response of plants to salt stress [25, 3840]. To further analyze the role of AsA in OsVTC1-1 -mediated enhancement of salt tolerance in rice, we examined the effect of AsA on salt tolerance of OsVTC1-1 RI seedlings with supplying exogenous AsA.…”
Section: Resultsmentioning
confidence: 99%
“…AtMYB12 is structurally related to the P1 regulator of flavone and phlobaphene biosynthesis in maize (Luo et al ., ). The high concentrations of flavonols produced in fruit were the consequence of AtMYB12 being able to activate expression of genes encoding enzymes of primary and intermediary metabolism, as well as those involved in flavonol metabolism (Zhang et al ., ,b). The ability of AtMYB12 to supply additional carbon skeletons, energy and reducing power for flavonoid biosynthesis, means that this TF can be used to enhance flavonoid production using a ‘push’ strategy.…”
Section: Improving the Concentrations Of Phytonutrients In Foodsmentioning
confidence: 99%
“…The ability of AtMYB12 to supply additional carbon skeletons, energy and reducing power for flavonoid biosynthesis, means that this TF can be used to enhance flavonoid production using a ‘push’ strategy. Thus, coexpression of AtMYB12 with Delila and Rosea 1 in tomato resulted in three‐fold higher concentrations of flavonols (120 mg g −1 DW) compared to tomatoes expressing AtMYB12 alone (40 mg g −1 DW), and almost double the concentrations of anthocyanins (5.8 mg g −1 DW) compared to fruit expressing Delila and Rosea1 (3.0 mg g −1 DW; Zhang et al ., ,b). Similarly, expression of AtMYB12 together with isoflavone synthase (IFS) for the synthesis of genistin in tomato, elevated the concentrations achievable in fruit from 1.6 μg g −1 DW (with IFS alone) to c .…”
Section: Improving the Concentrations Of Phytonutrients In Foodsmentioning
confidence: 99%
See 2 more Smart Citations